2018
DOI: 10.5152/tud.2018.74240
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in women with Cushing’s Syndrome: A controlled study

Abstract: Objective: The aim of this study is to determine the severity of female sexual dysfunction (FSD), quality of life, and depression status in female patients with Cushing's syndrome (CS). Material and methods:This study included 29 sexually active women with CS and 30 healthy age and body mass index matched women. The Female Sexual Function Index (FSFI) questionnaire, Beck Depression Inventory (BDI) and Short Form Health Survey (SF-36) were filled by each participant. Plasma levels of FSH, LH, PRL, cortisol, DHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…More specifically, lower scores for arousal, lubrication, orgasm, satisfaction and higher levels and frequency of pain during intercourse were found, while no differences were found for sexual desire. FSFI scores were positively correlated with LH levels (which were lower in the patient sample compared with controls) (44).…”
Section: Effects Of Active Disease On Quality Of Lifementioning
confidence: 83%
See 2 more Smart Citations
“…More specifically, lower scores for arousal, lubrication, orgasm, satisfaction and higher levels and frequency of pain during intercourse were found, while no differences were found for sexual desire. FSFI scores were positively correlated with LH levels (which were lower in the patient sample compared with controls) (44).…”
Section: Effects Of Active Disease On Quality Of Lifementioning
confidence: 83%
“…SF-36 results are low in physical and mental summary scores compared to healthy controls matched for age and sex (35,44). When compared to other untreated pituitary tumors (which not have been treated) CD were the patients with most impairment in all SF-36 measures (43).…”
Section: Effects Of Active Disease On Quality Of Lifementioning
confidence: 94%
See 1 more Smart Citation
“…An increase in LH increases androstenedione's production is converted to testosterone by 17β reductase in thecal cells and released into the blood (91). Androstenedione can also be converted to estradiol by the FSH-dependent aromatase enzyme in ovarian granulosa cells (92).…”
Section: Lh/fsh Ratiomentioning
confidence: 99%
“…Excessive circulating levels of glucocorticoids result in Cushing's syndrome (CS) (57). Only a single study analyzed the presence of SD in the case of CS (58). This is a case control study that showed that women with CS had lower FSFI scores with respect to healthy controls, 24 (88%) out of 29 CS women had a SD.…”
Section: Hypercortisolismmentioning
confidence: 99%